Scientific Literacy in Communicating Science and Socio-Scientific Issues: Prospects and Challenges - Li, Yanyan; Guo, Mengmeng (Frontiers in Psychology, 2021)
A holistic view of Scientific Literacy related literature was generated based on bibliometric analysis. The purpose was to provide insight into and knowledge on evolving knowledge fronts and to highlight the turning points in the existing literature between 1980 and 2019, as Scientific literacy in society can potentially help to answer unsolved riddles of Socio-Scientific Issues (SSI) to be a smart and responsible global citizen. Specifically, two decades before and after the year 2000 taken under account as it comprised most noticeable revolutionary developments in terms of economics, technology, culture and society. Interestingly, the attention paid to Scientific Literacy significantly increased after the financial crisis of 2008. International Journal of Science Education and the Journal of Research in Science Teaching were observed to be the top-cited and top publishing journals, respectively. Similarly, Jonathan Osborne, Rosalind Driver and Norman G. Lederman have recorded as the most cited and most published authors, respectively, during the study period. Alarmingly, most of the literature evolved in and was dominated by the Western region, indicating the need to understand the regional-cultural complexities of the East and the rest of the world. The recent evolving clusters, with the title of Literacy (as a concept), learning progression and informal reasoning observed as currently active knowledge areas in the evolution of the intellectual structure of the Scientific Literacy related literature. However, no recent trend or emerging research direction noticed in the last decade, even though, new and digital media (including immersive media) have revolutionized the communication channels and public understanding of science and socio-scientific issues.